Application of Artificial Intelligence Technology to Improve Responsiveness and Speed of Operations in Organizations - Silalahi, Verry Albert Jekson Mardame; Wardani, Febri Pramudya (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the application of artificial intelligence (AI) to improve the responsiveness and speed of organizational operations. In the digital era, AI is crucial in optimizing business processes by automating tasks, analyzing real-time data, and supporting data-driven decision-making. The study shows that AI plays a crucial role in accelerating market response, supply chain efficiency, and human resource management. While AI provides a competitive advantage, its success requires infrastructure readiness, workforce skills, and risk management. The results of this study offer effective AI implementation strategies and recommendations for further research on the long-term impact of AI on organizations and employees.